Effect of Yeast Selenium on Growth Performance, Muscle Selenium Deposition, and Antioxidant Capacity of Juvenile Cherax quadricarinatus - Ying Han; Chenchen Wang; Jimin Deng; Lizhen Zhong; Xiao Huang; Yuandong Sun; Xiaojuan Cui (Fishes)
This study aimed to investigate the effects of organic selenium-enriched yeast on the growth performance, muscle selenium deposition, and antioxidant capacity of juvenile Cherax quadricarinatus. Five experimental diets supplemented with 0.00 (control), 1.00, 2.00, 3.00, and 4.00 mg/kg of selenium-enriched yeast were fed to crayfish with an average initial body weight of (6.35 ± 1.66) g for 56 days. On days 0, 14, 28, 42, and 56 of the trial, 10 crayfish from each group were randomly sampled for body weight measurement. On day 28, the body weight of the crayfish fed diets containing 1.00, 2.00, 3.00, and 4.00 mg/kg selenium-enriched yeast was significantly higher (p < 0.05) than that of the control group. On day 56, the weight gain rate (WGR) and specific growth rate (SGR) of crayfish fed 1.00, 2.00, and 3.00 mg/kg selenium-enriched yeast were significantly elevated (p < 0.05) compared to those of the control group. Dietary selenium supplementation significantly enhanced muscle selenium deposition (p < 0.05), with deposition levels increasing proportionally to the supplementation levels within the same period. Selenium deposition initially increased, peaked at day 28 (significantly higher than the control), and then declined and stabilized. On day 42, the activities of pancreatic lipase (LPS), total superoxide dismutase (T-SOD), and acid phosphatase (ACP) in the hepatopancreas were significantly higher in the 3.00 and 4.00 mg/kg groups (p < 0.05). In comparison, trypsin activity was significantly increased in the 2.00 mg/kg and 3.00 mg/kg yeast selenium groups (p < 0.05). Alkaline phosphatase (AKP) activity was highly significantly elevated in the 2.00 mg/kg group (p < 0.01). On day 56, glutathione peroxidase (GSH-PX) activity in the hepatopancreas was considerably enhanced in all the selenium-supplemented groups (1.00–4.00) mg/kg (p < 0.05). In conclusion, the appropriate supplementation of selenium-enriched yeast promotes growth performance, enhances muscle selenium deposition, improves hepatopancreatic digestive enzyme activity, and strengthens antioxidant and immune capacities in Cherax quadricarinatus.